Horse Crazy! : The Complete Adventures of Bonnie and Sam - Lester, Alison; Pictures by Harvey, Roland (London Allen & Unwin, 2009)
One big book of the four fabulous Bonnie and Sam adventures
Including Illustrations
Keywords: Horses -- Children's stories, Australian -- Ponies